On the technical diagnostics of ball-bearing based on modelling of rotor-bearing systems by vibration method - Menh, Nguyen Cao (Vietnam Journal of Mechanics, 2007)
In this paper, after analysing deformations of loading ball-bearing it is able to investigate vibrations of rotor-bearing system as the system with non-linear and periodically varying stiffness. The modelling of the systems is depent on properties of the shaft (rigid or flexible) and on measurement techniques for system vibrations (by eddy current proximity probe for rotating shaft or on non-rotating parts of the rotor-bearing systems) it can be described by a single degree-of-freedom or two-degree-of freedom nonlinear systems subjected to parametric and external excitations. Therefore it is possible to obtain different characteristics of system vibrations with respect to different defects of ball-bearing. These symptoms help us to identify and estimate the bearing quality by measurement and analysis of system vibrations.